The impact of security to Indonesian foreign policy / Adnan Nasution Seniwati - Adnan Nasution, Seniwati (2010)
Indonesian politics opened a new phase of democratization after Soeharto stepped down from his 32 years of authoritarian rule. In this paper, Indonesia's foreign policy changes after Soeharto are systematically examined through an ‘international pressure–such as security. This model specifies that Indonesia's foreign policy during democratization is mainly influenced by one factor: security of the new democratic government. Four cases of foreign policy decision-making from three post-Soeharto presidencies are examined: (i) Indonesia's East Timor policy under Habibie; (ii) Indonesia's ‘silence response’ toward China's protest on the anti-Chinese riots under Habibie; (iii) Wahid's ‘looking towards Asia’ proposal; and (iv) Megawati's anti-terrorism and Aceh military operation. The results show that security shapes the nature of state behavior, i.e. balancing or compromising, whereas international pressure determines the pattern of state behavior, i.e. external/internal balancing or compromising in words/in deeds